Development of a radiopaque, long-term drug eluting bioresorbable stent for the femoral-iliac artery. Issue 59 (28th October 2019) - Ha, Dong-Heon; Kim, Jae Yun; Park, Tae Sik; Park, Jong Ha; Chae, Suhun; Kim, Byoung Soo; Lee, Han Cheol; Cho, Dong-Woo
Abstract : A radiopaque, long-term drug eluting bioresorbable stent is developed for the treatment of femoral-iliac artery. The prepared materials are printed on a pre-designed rotating rod. The fabricated stent can be adapted for various clinical cases. Abstract : Tubular tissues exist in various forms purported for blood supply, waste secretion, etc. to aid proper function and maintenance of the human body. Under pathological conditions, however, these tissues may undergo stenosis. A major surgical treatment for stenosis is to implant a medical device called a stent which aims to expand the narrowed tissue and maintain its patency. Most stents are currently made from metals; despite their high mechanical strength, however, interactions with the host tissue often results in restenosis and stent fracture. To solve these problems, a bioresorbable stent (BRS) is proposed as a next generation stent. In this study, a rotating rod combined 3D printing system was developed to fabricate various types of BRSs. In addition, we confirmed that a 1.5 year long-term release of paclitaxel is possible using polymeric materials. Moreover, a stent loaded with contrast powder was fabricated and was successfully viewed under fluoroscopy. The stent was then implanted in the iliac arteries of pigs and no adverse events were observed for up to 8 weeks.